2002
DOI: 10.1046/j.1432-1033.2003.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of activated Factor XII to endothelial cells affects its inactivation by the C1‐esterase inhibitor

Abstract: It is well known that activated Factor XII (FXIIa) and kallikrein are rapidly inactivated in plasma as a result of reaction with endogenous inhibitors. The purpose of this may be to prevent uncontrolled deleterious spreading and activation of target zymogens. Both FXII and the complex plasma prekallikrein/high molecular mass kininogen become activated when they bind, in a Zn 2+ -dependent manner, to receptors on human umbilical vein endothelial cells (HUVEC). The C1-esterase inhibitor (C1-INH) is by far the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…Other pathways of bradykinin formation exist, however, contact system activation is the main mediator of attacks of angioedema according to literature [25]. Possibly, FXIIa was formed but we were unable to measure it because C1INH cannot (efficiently) inhibit FXIIa, when it is bound to endothelial cells [26]. Furthermore, enzyme-C1INH complexes are rapidly cleared from the circulation possibly obscuring differences in complex concentrations [27–29].…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways of bradykinin formation exist, however, contact system activation is the main mediator of attacks of angioedema according to literature [25]. Possibly, FXIIa was formed but we were unable to measure it because C1INH cannot (efficiently) inhibit FXIIa, when it is bound to endothelial cells [26]. Furthermore, enzyme-C1INH complexes are rapidly cleared from the circulation possibly obscuring differences in complex concentrations [27–29].…”
Section: Discussionmentioning
confidence: 99%
“…As it has previously been shown that FXIIa binds to the cells in a manner identical to FXII [9], binding of FXIIa was used to quantify relatively the amount of FXII bound to cholesterol‐depleted cells. Normal and cholesterol‐depleted cells in 12‐well microtiter plates were incubated with FXIIa, as described above, and analyzed for the amidolytic activity of cell‐bound FXIIa, as previously described [12]. To each well was added 600 µL of 0.8 m m S‐2302 in 50 m m Tris, 12 m m NaCl, 10 m m EDTA, pH 7.8.…”
Section: Amidolytic Activity Of Cell‐bound Fxiiamentioning
confidence: 99%
“…Increased levels of cystatin C, a cysteine protease, are observed in obese subjects and associate with CVD [19,20]. Serpin G1, better known as C1 inhibitor, is an inhibitor of kallikrein and factor IIa [21]. Serpin F2 or α-2-antiplasmin, is the primary inhibitor of plasmin in the circulation [22].…”
Section: Introductionmentioning
confidence: 99%